การศึกษาเชิงวิเคราะห์สารัตถธรรมที่ปรากฏในชินกาลมาลีปกรณ์ เพื่อพัฒนานักศึกษาตามแนวพระพุทธศาสนา - ป้อมสุวรรณ์ ประยูร (Academic Journal Phranakhon Rajabhat University, 2017)
Research Functional analysis of the fair exposition in Mali’s interim study were to develop along this Buddhism. A study to analyze And synthetic The events in Buddhism especially memorable and historic events took a pretty good model used in the study and development. This research aims to study the functional justified in Mali’s interim exposition. The researchers analyzed the processes used to analyze principles. And take the main event worth preserving application guide the students to achieve a good Buddhist. The synthesis of the principles right. Research found that In Mali’s interim Exposition, the event is a good example, which contains the main principles such as intellectual precepts, meditation or threefold in the rule of the king in the era of Buddhism. The main object Sangahavatthu The unity of the people against each other and their parents. Keeping the Faith Creating such a pagoda temple built Doctrinal. Event suitable for applications such as preaching to develop competition to build the pagoda. Or a great city to compete for the killing. The kindness to take kenhantns Buddhist worship. In the past, the assistance of major cities in the region do not struggle to expand. Because people upset The parents of the woman or give her a great example. Her parents Chamadevi key role creeks finish. To be fair to give homage to the city as bait in any other city of kings and rulers. The Buddha and the monks represent another tribute.